1698. Trends in antimicrobial resistance among outpatient urine E. coli isolates in US females ≥12 years of age: A multicenter evaluation from 2011 to 2019. (31st December 2020) - Kaye, Keith S; Gupta, Vikas; Mulgirigama, Aruni; Joshi, Ashish V; Scangarella-Oman, Nicole; Yu, Kalvin; Ye, Gang; Mitrani-Gold, Fanny S
Abstract: Background: E. coli is the predominant uropathogen isolated in uncomplicated urinary tract infections (UTI). Surveillance data suggest increasing antimicrobial resistance (AMR), although recent data from the outpatient setting are limited. Treatment is typically empiric and should be guided by local resistance rates; however, this is challenging in the absence of routine culture and assessment of regional AMR. We characterized AMR trends for E. coli isolated from females with outpatient UTI in the US, from 2011 to 2019. Methods: A retrospective multicenter cohort study of antimicrobial susceptibility using data from the BD Insights Research Database (Franklin Lakes, NJ) was conducted. The first E. coli urine culture isolates representing each distinct susceptibility pattern within 30 days of index urine from 2011–2019 were included from females ≥ 12 years old. E. coli isolates were identified as not-susceptible (NS) if intermediate or resistant to trimethoprim-sulfamethoxazole (TMP-SMX NS), fluoroquinolone (FQ NS), nitrofurantoin (NFT NS), ESBL+ (by commercial panels or intermediate/resistant to ceftriaxone, cefotaxime, ceftazidime or cefepime), and multi-drug resistant (MDR), defined as NS to ≥ 2 or ≥ 3 of FQ, TMP-SMX, NFT or ESBL+. Descriptive analyses characterized AMR (%) over time and generalized estimating equations were used to statistically assess AMR trends over time. Results: A total of 1, 513, 882 E. coli isolates were tested at 106 to 295 US centers between 2011 and 2019. Over the study period, AMR remained persistently high (> 20%) for FQ and TMP-SMX and increased for the MDR (≥ 3 drugs) phenotype (from 3.1% to 4.0%) (Table). Prevalence of the ESBL+ phenotype increased year-on-year (from 4.1% to 7.3%). Modeling confirmed a significant increasing trend for the ESBL+ (7.7%/year) and MDR (≥ 3 drugs) phenotypes (2.7%/year) (P< 0.001), with decreasing or no trend change for NFT NS and other AMR phenotypes (Table). Table. Descriptive Statistics and Model-estimated Annual Change of AMR (count and % not-susceptible out of isolates tested) in E. coli among US Females (≥12 years of age) with Outpatient UTI Conclusion: Characterization of AMR trends for E. coli over the last decade, in outpatient E. coli isolates in US females, shows persistently high AMR to FQ and TMP-SMX, and increasing AMR trends for the ESBL+ and MDR (≥ 3 drugs) phenotypes. Disclosures: Vikas Gupta, PharmD, BCPS, Becton, Dickinson and Company (Employee, Shareholder)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Aruni Mulgirigama, MBBS, GlaxoSmithKline plc. (Employee, Shareholder) Ashish V. Joshi, PhD, GlaxoSmithKline plc. (Employee, Shareholder) Nicole Scangarella-Oman, MS, GlaxoSmithKline plc. (Employee, Shareholder) Kalvin Yu, MD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Gang Ye, PhD, Becton, Dickinson and Company (Employee)GlaxoSmithKline plc. (Other Financial or Material Support, Funding) Fanny S. Mitrani-Gold, MPH, GlaxoSmithKline plc. (Employee, Shareholder)